Ebaco-R: Refinement of organizational commitment bases scale - Leandro Trigueiro-Fernandes; Marcos Luiz Lins Filho; Anderson Luiz Rezende Mól; Miguel Eduardo Moreno Añez (BBR: Brazilian Business Review)
Despite being extensively studied, the organizational commitment still remains in the research agenda due to a lack of consensus on conceptual and structural issues. Therefore, this research proposed to refine the Organizational Commitment Bases Scale (EBACO) in search for an instrument with better psychometric properties and a better theoretical adjustment. The research was divided into two phases, the first one was eminently exploratory, carried out with 149 observations, and evaluated the EBACO’s psychometric fitting with the reduction of two bases. The second phase, confirmatory, occurred in 45 organizations - 27 public and 18 private, with 812 observations. The confirmatory factor analysis was adopted to evaluate the psychometric properties and the theoretical adequacy of the refined model. The results indicated that with five dimensions the EBACO model presented higher levels of KMO, Cronbach’s Alpha, and explained variance. It was also verified that the model discussed obtained adequate values of the goodness of fit indexes χ2/df, RMSEA, CFI, TLI and RMR. Finally, it was verified that the refined model, EBACO-R, presented a convergent validity, ensuring a greater suitability of the scale to the theory. Furthermore, the model refinement, excluding the bases, contributes to the discussion by Osigweh (1989) about the 'concept stretching' commitment.